Growth Optimisation and Kinetic Profiling of Diesel Biodegradation by a Cold-Adapted Microbial Consortium Isolated from Trinity Peninsula, Antarctica - Roslee, Ahmad Fareez Ahmad; Gomez Fuentes, Claudio German; Zakaria, Nur Nadhirah; Shaharuddin, Nor Azmi; Zulkharnain, Azham; Khalil, Khalilah Abdul; Convey, Peter; Ahmad, Siti Aqlima (My University, 2021)
Simple Summary Diesel fuel is very crucial for anthropogenic activities in Antarctica and the surges in annual demand mean higher likelihood of spillages from improper handling during transportation, storage and disposal processes. The impacts can be very extensive or well-contained depending on the scale of the spills as well as the terrain involved. Nevertheless, the freezing temperature and prolonged solar irradiance in the south pole greatly hampered the natural attenuation and photovolatilisation of petrogenic hydrocarbons, contributing to their persistency. The most susceptible groups are the soil microorganisms, mosses, seabirds and pinnipeds as they are easily found near the shore where hydrocarbons spillage is very common. Microbial bioremediation is a well-established approach in restoring many hydrocarbons-polluted areas, thus the current study focused on the optimisation and application of locally isolated microbial consortium to simulate the in situ diesel clean-up process in aqueous medium. This study highlights the ability of the selected consortium to degrade diesel almost completely at moderately low temperature, suggesting its potential application in Antarctic settings. Pollution associated with petrogenic hydrocarbons is increasing in Antarctica due to a combination of increasing human activity and the continent's unforgiving environmental conditions. The current study focuses on the ability of a cold-adapted crude microbial consortium (BS24), isolated from soil on the north-west Antarctic Peninsula, to metabolise diesel fuel as the sole carbon source in a shake-flask setting. Factors expected to influence the efficiency of diesel biodegradation, namely temperature, initial diesel concentration, nitrogen source type and concentration, salinity and pH were studied. Consortium BS24 displayed optimal cell growth and diesel degradation activity at 1.0% NaCl, pH 7.5, 0.5 g/L NH4Cl and 2.0% v/v initial diesel concentration during one-factor-at-a-time (OFAT) analyses. The consortium was psychrotolerant based on the optimum growth temperature of 10-15 degrees C. In conventionally optimised media, the highest total petroleum hydrocarbons (TPH) mineralisation was 85% over a 7-day incubation. Further optimisation of conditions predicted through statistical response-surface methodology (RSM) (1.0% NaCl, pH 7.25, 0.75 g/L NH4Cl, 12.5 degrees C and 1.75% v/v initial diesel concentration) boosted mineralisation to 95% over a 7-day incubation. A Tessier secondary model best described the growth pattern of BS24 in diesel-enriched medium, with maximum specific growth rate, mu(max), substrate inhibition constant, K-i and half saturation constant, K-s, being 0.9996 h(-1), 1.356% v/v and 1.238% v/v, respectively. The data obtained suggest the potential of microbial consortia such as BS24 in bioremediation applications in low-temperature diesel-polluted soils.
Keywords: diesel; microbial consortium; biodegradation; response-surface methodology (rsm); kinetic model